(untitled) (Journal of Libya for geographical studies, 2022)
The research aims to apply the spatial analysis methodology for the role of tourist accommodation in Misurata region by using geographic information systems (GIS) and the spatial analysis tools available within the GIS program (Arc GIS Spatial Analysis) which are characterized by their abilities to analyze the data associated with the metadata base by identifying the characteristics of the place, studying the spatial relationships of the geographical phenomenon, and the pattern of its distribution in the study area. The study relied on the descriptive analytical approach in data processing, through the use of some statistical methods, graphic representation, and cartography; In order to highlight the spatial characteristics of the sites and types of tourist accommodations and determine the pattern of their geographical distribution in Misurata. This study used the method of field survey in accordance with the data of the year 2021, identifying their locations by using the Global Positioning System (GPS) device in order to build a spatial database using GIS, and represent these sites on the map of the study area. The study reveals the density distribution pattern for the sites of tourist accommodation through the application of neighborhood link analysis, density analysis. The results show a clear variation in the geographical distribution of tourist accommodation sites; moreover, the distribution pattern of these sites within the region is the clustered pattern, meaning the direction of the distribution pattern is linked with the direction of urban growth and the concentration of other public services. Most of the sites of tourist accommodations are concentrated in the center and are not distributed in an orderly fashion over the entire area. The study also shows that geographic information systems have a great potential in the ability to prepare a tourist database and digital maps.